New life for old cellular pathology: a transformational approach to the upcycling of historic e-pathology records for contemporary clinical uses. Issue 4 (16th February 2021) - Rew, David Anthony; Hales, Alan Arthur; Cable, David; Burrill, Keith; Bateman, Adrian C
Abstract : Aims: Cellular pathology ('e-pathology') record sets are a rich data resource with which to populate the electronic patient record (EPR). Accessible reports, even decades old, can be of great value in contemporary clinical decision making and as a resource for longitudinal clinical research. The aim of this short paper is to describe a solution in a major UK University Hospital which gives immediate visibility and clinical utility to 30 years of e-pathology records Methods: Over the past decade, we have created a timeline structured and iconographic data framework for the 'whole-of-life' visualisation of the entirety of an EPR. We have enhanced this interface with the sequential extraction of 373 342 e-pathology reports from legacy Ferranti (1990–1997) and Masterlab (1997–2004) files. They have been uploaded into our SQL file servers, following appropriate data quality and patient identity reconciliation checks. Results: We have restored a large repository of previously inaccessible e-pathology records to clinical use and to immediacy of access as a foundation element of our timeline structured EPR. This process has also allowed us to populate and validate an EPR-integral breast cancer data system of 20 000 cases with e-pathology records dating back to 1990. Conclusions: The revitalisation of old e-pathology reports into a timeline structured EPR creates preserves and upcycles the investment in pathology reporting which is otherwise progressively lost to clinical use. E-pathology records provide reliable, life-long evidence of critical transition points in individual lives and disease progression for clinical and research use, when they can be instantly accessed.